Focused Cardiac Ultrasound to Detect Pre-capillary Pulmonary Hypertension - Lyssens, Aurélie; Lekane, Marine; Gommeren, Kris; Merveille, Anne-Christine (Frontiers in Veterinary Science, 2022)
BACKGROUND: Early recognition of pre-capillary (PC) pulmonary hypertension (PH) benefits dogs, allowing earlier treatment and improving prognosis. The value of Focused Cardiac Ultrasound (FCU) to diagnose PH and assess its severity has not been investigated yet. HYPOTHESIS: A subjective 10-point FCU pulmonary hypertension score (PHS) allows diagnosis and assessment of severity of PCPH. ANIMALS: Fifty client-owned dogs. METHODS: Dogs, recruited between September 2017 and February 2020 were classified into 4 categories (no, mild, moderate and severe PH, C1 to C4 respectively). C1 and C2, and C3 and C4 were regrouped as group1 and group2 respectively. A blinded general practitioner assessed 4 FCU cineloops. Five echocardiographic parameters were subjectively scored, resulting in a total score of 0 to 10. Non-parametric tests compared global scores between categories and groups. A receiver-operating characteristic (ROC) curve determined the cut-off value to differentiate group 1 and group 2. A grey zone approach allowed diagnosing or excluding moderate to severe PH with 90% certitude. RESULTS: Global scores were significantly higher for C4 than C1, C2 and C3. Global scores of G2 were significantly higher than G1. The ROC curve indicated a cut-off value of 5, discriminating group1 from group2 with a sensitivity of 77% and a specificity of 100%. A score of ≥5/10 allowed diagnosing moderate to severe PH with ≥90% certainty while a score of ≤2/10 excluded PH with ≥90% certainty. CONCLUSIONS AND CLINICAL SIGNIFICANCE: Moderate to severe PCPH can be accurately detected by non-cardiologists using a 10-point FCU PHS score.